The story of me - Jones, Stanton L.; Jones, Brenna B.; Spector, Joel (Colorado Springs, CO : NavPress, 1995)
Lays a spiritual foundation for the child's understanding of his or her sexuality. Develop an appreciation for God's marvelous gift by understanding some of the basics of human reproduction. Discusses the growth of a child inside the mother's body and the birth process.
"Designed for parents to read to their child at ages 3 through 5."
Keywords: Human reproduction -- Juvenile literature; Human reproduction -- Religious aspects -- Christianity -- Juvenile literature; Sex (Biology) -- Juvenile literature; Sex instruction for children; Sex instruction for youth -- Religious aspects -- Christianity; Christian life; Human reproduction; Human reproduction -- Religious aspects -- Christianity; Sex (Biology); Sex instruction for children; Juvenile works